Pengaruh Social Media Marketing, Kepercayaan, Kesadaran, dan Citra Merek terhadap Keputusan Pembelian melalui e-WOM - Karo Ummah, Fadia; Koranti, Komsi; Noviyana, Syntha; Sriyanto (Journal of Trends Economics and Accounting Research, 2025)
Advances in information technology have made it easier for users to access information through digital media, especially social media. This study aims to analyze the direct influence of social media marketing, trust, brand awareness, brand image, and electronic word of mouth (e-WOM) on purchase decisions; to analyze the indirect influence of social media marketing, trust, brand awareness, and brand image on purchase decisions for Homskin products through electronic word of mouth (e-WOM); and to identify the most dominant variable. This research uses primary data collected from 150 respondents through a Google Form questionnaire. Data were analyzed using partial least squares–structural equation modeling (PLS-SEM) with the assistance of SmartPLS 4.0. The results indicate that social media marketing, trust, brand awareness, and brand image have a positive direct effect on e-WOM and purchase decisions. e-WOM is proven to function as an intervening variable between social media marketing, trust, brand awareness, and brand image on purchase decisions for Homskin products. Social media marketing has the most dominant influence on both e-WOM and purchase decisions.